Safety of cochlear implantation before 12 months of age: Medical University of South Carolina and Pediatric American College of Surgeons–National Surgical Quality improvement program outcomes. (26th August 2015) - O'Connell, Brendan P.; Holcomb, Meredith A.; Morrison, Daniel; Meyer, Ted A.; White, David R.
Abstract : Objectives/Hypothesis: The primary objective of this study was to determine the safety profile of cochlear implantation (CI) in infants <12 months old. Study Design: Retrospective review of institutional (Medical University of South Carolina [MUSC]) and national data (Pediatric American College of Surgeons–National Surgical Quality Improvement Program [ACS‐NSQIP]). Methods: Cases were subdivided into two groups according to age at CI: <12 months and 12 to 18 months. The primary outcome measure of interest was occurrence of a postoperative medical or surgical complication. Operative time, anesthesia time, time in the postoperative anesthesia care unit, and length of stay were also assessed. Results: In infants <12 months of age, the incidence of a 30‐day postoperative surgical complication using the ACS‐NSQIP database was 3.6%; this did not differ from the rate observed in the 12‐ to 18‐month‐old group (3.2%, P = 1.0). In the MUSC series, the occurrence of a 30‐day postoperative complication in children <12 months old was comparable (2.7%). At longer‐term follow‐up (mean = 3.7 years), the incidence of a postoperative surgical complication in infants <12 months old using MUSC data was 13.5%. When compared to older children at longer‐term follow‐up, no difference was noted (12.7%, P = 1.0). The incidence of a postoperative medical or anesthetic complication in children <12 months of age was extremely rare in both MUSC and ACS‐NSQIP series (0% and 1.3%, respectively). Conclusions: Institutional and national data demonstrate that CI in children <12 months of age is a safe procedure. Although infants <12 months old are at risk for postoperative complications, the rates of surgical and medical complications were no different compared to children 12 to 18 months of age. Level of Evidence: 4 Laryngoscope, 126:707–712, 2016